2013
DOI: 10.3389/fendo.2013.00084
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Subcellular Distribution of n-Octanoyl or n-Decanoyl Ghrelin in Ghrelin-Producing Cells

Abstract: Background: The enzyme ghrelin O-acyltransferase (GOAT) catalyzes the acylation of ghrelin. The molecular form of GOAT, together with its reaction in vitro, has been reported previously. However, the subcellular processes governing the acylation of ghrelin remain to be elucidated.Methods: Double immunoelectron microscopy was used to examine changes in the relative proportions of secretory granules containing n-octanoyl ghrelin (C8-ghrelin) or n-decanoyl ghrelin (C10-ghrelin) in ghrelin-producing cells of mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The next issue was to determine if this higher available stomach C8:0 level influenced the stomach total ghrelin expression and increased the concentration of circulating acylated ghrelin, after the action of the gastric GOAT enzyme. Indeed, Nishi et al detected heptanoylghrelin [ 25 ] or decanoylghrelin [ 48 ] in the stomachs of mice fed with triheptanoin or tricaprin. This suggests that ingested MCFAs were directly utilized for the ghrelin acylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next issue was to determine if this higher available stomach C8:0 level influenced the stomach total ghrelin expression and increased the concentration of circulating acylated ghrelin, after the action of the gastric GOAT enzyme. Indeed, Nishi et al detected heptanoylghrelin [ 25 ] or decanoylghrelin [ 48 ] in the stomachs of mice fed with triheptanoin or tricaprin. This suggests that ingested MCFAs were directly utilized for the ghrelin acylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when related to dietary lipids and especially dietary MCFAs, the importance of the so-called GOAT-ghrelin-GHSR-1a axis on these parameters is unclear. Nishi et al [ 48 ] found no effect on body weight and food intake after feeding mice during two weeks with diets enriched in tricaprylin or tricaprin compared to control diets. However, feeding GOAT-null mice with MCT-enriched diets during 8 weeks resulted in significantly lower body weight compared with control mice [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rodent studies support the concept that circulating acyl-ghrelin levels are at least in part dependent on nutritional availability of MCFAs (16). This observation is supported by studies of Nishi et al (17), who showed that the amount of C8 or C10 acyl-ghrelin content in the stomach depends on nutritional conditions. Ingestion of the medium-chain triglyceride, glycerol triheptanoate, which is not naturally synthesized by mammalian cells, resulted in the production of n-heptanoyl-ghrelin, which was found both in the circulation and in the stomach of the animals (16).…”
Section: Discussionmentioning
confidence: 64%
“…Indeed, ingestion by mice of either MCFAs or MCTs increased the stomach concentration of acylated ghrelin (Nishi, Hiejima, Hosoda, et al, 2005), without changing the total ghrelin amounts. Nishi et al detected heptanoylghrelin (Nishi, Hiejima, Hosoda, et al, 2005) or decanoylghrelin (Nishi et al, 2013) in the stomachs of mice fed with triheptanoin or tricaprin, confirming that at least part of the ingested MCFAs was directly used for ghrelin acylation. These results are consistent with the hypothesis of gastric absorption of MCTs but part of the caprylic acid present in the stomach may also come from intestinal absorption followed by uncompleted uptake by the liver.…”
Section: Impact Of Dietary Sfas On Cellular Protein Acylationmentioning
confidence: 98%